2008
DOI: 10.1681/asn.2007111261
|View full text |Cite
|
Sign up to set email alerts
|

CTGF Inhibits BMP-7 Signaling in Diabetic Nephropathy

Abstract: In diabetic nephropathy, connective tissue growth factor (CTGF) is upregulated and bone morphogenetic protein 7 (BMP-7) is downregulated. CTGF is known to inhibit BMP-4, but similar cross-talk between BMP-7 and CTGF has not been studied. In this study, it was hypothesized that CTGF acts as an inhibitor of BMP-7 signaling activity in diabetic nephropathy. Compared with diabetic wild-type CTGF ϩ/ϩ mice, diabetic CTGF ϩ/Ϫ mice had approximately 50% lower CTGF mRNA and protein, less severe albuminuria, no thickeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 36 publications
9
113
4
Order By: Relevance
“…Also, albuminuria was less pronounced in diabetic CTGF 1/2 compared with diabetic wild-type mice (Nguyen et al 2008a). To this we add that pSmad1/5/8 was mainly localized in podocytes.…”
Section: Ctgf Is Upregulated Whereas Sostdc1 Is Decreased In Diabetimentioning
confidence: 86%
See 1 more Smart Citation
“…Also, albuminuria was less pronounced in diabetic CTGF 1/2 compared with diabetic wild-type mice (Nguyen et al 2008a). To this we add that pSmad1/5/8 was mainly localized in podocytes.…”
Section: Ctgf Is Upregulated Whereas Sostdc1 Is Decreased In Diabetimentioning
confidence: 86%
“…Exogenous recombinant human CTGF reduced pSmad1/5/8 level in the renal cortex, indicating that CTGF level significantly affects renal BMP signaling activity (Nguyen et al 2008a). Moreover, inhibition of CTGF attenuated experimental diabetic nephropathy in at least three independent and fundamentally distinct studies involving neutralizing anti-CTGF antibodies, CTGF antisense oligonucleotides, and genetic deletion of one CTGF allele (CTGF 1/2 ) (Flyvbjerg et al 2004;Guha et al 2007;Nguyen et al 2008a;Yokoi et al 2008). In a previous study, we observed a decrease of pSmad1/5/8 abundance in diabetic CTGF 1/1 as compared with CTGF 1/2 mice in Western blots of total renal cortex (Nguyen et al 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…However, CTGF can also activate TGF-b1 and inhibit the antifibrotic effects of BMP-7 (282,283). In both experimental and human renal allografts, CTGF is overexpressed in fibrotic kidneys and may represent a biomarker of renal fibrosis (284).…”
Section: Connective Tissue Growth Factormentioning
confidence: 99%
“…This mosaic structure has resulted in CTGF and other CCN proteins being implicated both directly and indirectly in a vast array of biological processes and has made it difficult to predict the function of CTGF in any given biological context (Holbourn, Acharya et al 2008;Chen and Lau 2009). However, there is a growing body of evidence that CTGF acts to connect cells to the microenvironment by providing adhesive signals (Gao and Brigstock 2006;Hoshijima, Hattori et al 2006) as well as modulating the availability and function of soluble growth factors A c c e p t e d M a n u s c r i p t 4 (Abreu, Ketpura et al 2002;Hashimoto, Inoki et al 2002;Nguyen, Roestenberg et al 2008). Thus, the tissue context within which CTGF is expressed is likely to play a key role in determining its biological function in any given microenvironment.…”
Section: Introductionmentioning
confidence: 99%